Survival outcomes following laparoscopic versus open D3 dissection for stage II or III colon cancer (JCOG0404): a phase 3, randomised controlled trial. (April 2017) - Kitano, Seigo; Inomata, Masafumi; Mizusawa, Junki; Katayama, Hiroshi; Watanabe, Masahiko; Yamamoto, Seiichiro; Ito, Masaaki; Saito, Shuji; Fujii, Shoichi; Konishi, Fumio; Saida, Yoshihisa; Hasegawa, Hirotoshi; et al.
Summary: Background: Although benefits of laparoscopic surgery compared with open surgery have been suggested, the long-term survival of patients undergoing laparoscopic surgery for colon cancer requiring Japanese D3 dissection remains unclear. We did a randomised controlled trial to establish non-inferiority of laparoscopic surgery to open surgery. Methods: We did an open-label, multi-institutional, randomised, two-arm phase 3 trial in 30 hospitals in Japan. Patients aged 20–75 years who had histologically proven colon cancer; tumours located in the caecum or ascending, sigmoid, or rectosigmoid colon; T3 or deeper lesions without involvement of other organs, node stages N0–2, and metastasis stage M0; and tumour size of 8 cm or smaller were included. Only accredited surgeons did surgery as an operator or instructor. Patients were randomly assigned (1:1) preoperatively to undergo D3 resection either by an open route or a laparoscopic route, via phone call or fax to the Japan Clinical Oncology Group (JCOG) Data Center. Randomisation used a minimisation method with a biased-coin assignment according to tumour location (caecum, ascending vs sigmoid, rectosigmoid) and institution. The primary endpoint was overall survival and was analysed by intention to treat. The non-inferiority margin for the hazard ratio (HR) was set at 1·366. This study is registered with UMIN Clinical Trials Registry, number C000000105, andClinicalTrials.gov, numberNCT00147134 . Findings: Between Oct 1, 2004, and March 27, 2009, 1057 patients were randomly assigned to either open surgery (n=528) or laparoscopic surgery (n=529). 5-year overall survival was 90·4% (95% CI 87·5–92·6) for open surgery and 91·8% (89·1–93·8) for laparoscopic surgery. Laparoscopic D3 surgery was not non-inferior to open surgery for overall survival (HR 1·06, 90% CI 0·79–1·41; pnon-inferiority =0·073). 65 (13%) patients in the open surgery group and 53 (10%) patients in the laparoscopic surgery group had grade 2–4 adverse events. Grade 2–4 adverse events included diarrhoea (15 [3%] in the open surgery group vs 14 [3%] in the laparoscopic surgery group), paralytic ileus (six [1%] vs nine [2%]), and small intestine bowel obstruction (16 [3%] vs 11 [2%]). Two treatment-related deaths occurred in the open surgery group: one patient died 7 days after surgery (probably due to myocardial infarction), and one patient died from febrile neutropenia, pneumonia, diarrhoea, and gastrointestinal haemorrhage during postoperative chemotherapy. Interpretation: Laparoscopic D3 surgery was not non-inferior to open D3 surgery in terms of overall survival for patients with stage II or III colon cancer. However, because overall survival in both groups was similar and better than expected, laparoscopic D3 surgery could be an acceptable treatment option for patients with stage II or III colon cancer. Funding: National Cancer Center Research and Development Fund, Grant-in-Aid for Cancer Research, and Health and Labour Sciences Research Grant for Clinical Cancer Research from the Ministry of Health, Labour and Welfare of Japan.